Development of the Fog Seal Layer Characterized by Durability in Terms of Skid Resistance. (5th November 2021) - Jiang, Yingjun; Fan, Jiangtao; Lv, Pengyu; Yuan, Kejia; Yi, Yong; Tian, Tian; Bai, Chenfan
Abstract : In this paper, based on the thermosetting properties, bonding performance, high-temperature water damage resistance, and aging resistance properties of epoxy-emulsified asphalt, the best formulation of epoxy emulsified asphalt as a skid resistance fog sealing asphalt is studied. Through accelerated wheel wear and other tests, the effects of the ratio of the amount of skid resistance particles to the amount of epoxy emulsified asphalt, the total amount of skid resistance fog seal asphalt, and the construction process on the skid resistance durability of the skid resistance fog seal were studied. The results show that the epoxy emulsified asphalt formula code A80 (E2 ) (emulsified asphalt : water-based epoxy = 80 : 20) is the best formula; when the proportion of emery and epoxy emulsified asphalt is 1 : 1, the British Pendulum Number (BPN) reduction rate of the skid resistance fog seal-test piece worn 100, 000 times was 27.4%. Compared with the same period, the reduction rate was reduced by 4.6% on average, with the smallest mass loss rate and the best skid resistance durability. When the total amount of skid resistance fog seal asphalt is 1.2 kg/m 2, the BPN reduction rate of the skid resistance fog seal specimen worn 100, 000 times was 27.4%, which is an average reduction of 5.8% over the same period, and the mass loss rate is the smallest, and the skid resistance durability optimal. When using the premixed process, the BPN of the specimen was reduced by 13.2% after abrasion of 100, 000 times. Compared with the "one asphalt and one sand" and "double asphalt and one sand" molded specimens, the mass loss rate was reduced by 15.0%, 4eU&7.2%, showing the best skid resistance performance. The results can provide guidance for the design and construction of AC-13 and other pavement skid resistance fog seals.